Recent Progresses in the Multicomponent Synthesis of Dihydropyridines by Applying Sustainable Catalysts Under Green Conditions - Sonali Anantha, Immandhi Sai; Kerru, Nagaraju; Maddila, Suresh; Jonnalagadda, Sreekantha B. (Frontiers in Chemistry, 2021)
The synthesis of dihydropyridines, valuable molecules with diverse therapeutic properties, using eco-friendly heterogeneous catalysts as a green alternative received significant consideration. By selecting appropriate precursors, these compounds can be readily modified to induce the desired properties in the target product. This review focused on synthesising diverse dihydropyridine derivatives in single pot reactions using magnetic, silica and zirconium-based heterogeneous catalytic systems. The monograph describes preparation techniques for various catalyst materials in detail. It covers facile and benign magnetic, silica, zirconium-based and ionic liquid catalysts, exhibiting significant efficacy and consistently facilitating excellent yields in short reaction times and cost-effective way. Most of the designated protocols employ Hantzsch reactions involving substituted aldehydes, active methylene compounds and ammonium acetate. These reactions presumably follow Knoevenagel condensation followed by Michael addition and intra molecular cyclisation. The multicomponent one-pot protocols using green catalysts and solvents have admirably increased the product selectivity and yields while minimising the reaction time. These sustainable catalyst materials retain their viability for several cycles reducing the expenditure are eco-friendly.